Analisis N Total dan Kandungan Logam Berat Cu dan Zn pada Tanah Sawah di Daerah Pengairan Sungai Cikijing Kecamatan Rancaekek - Agustine, Leony; Sudirja, Rija; Harryanto, Rachmat (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 7 No 1 (2022), 2022)
This study aims to determine: 1) evaluate the distribution of total N and the distribution of heavy metals Cu and Zn in paddy fields in the Cikijing River Irrigation Area, Rancaekek District, 2) the amount of total N and the distribution of heavy metals Cu and Zn in paddy fields in the Cikijing River Irrigation Area, Rancaekek District. The experiment was conducted in paddy fields contaminated with factory waste in the Cikijing River Watershed, Rancaekek District and followed with the analysis of the soil at the Laboratory of Soil Fertility and Plant Nutrition, Faculty of Agriculture, Padjadjaran University. The experiment was conducted in February 2017 to November 2017. The determination of sample points is based on Homogeneous Soil Map Unit (SLH), which is made by overlay map on the map of soil types, slope maps and land use maps of research areas. The number of samples is 8, which is located on the 5 villages. The variables observed and measured in this study included total N and heavy metals Cu and Zn. The results showed that the total N in the research area was low and moderate, but at some location points there was a very low N content, while heavy metal Cu at several locations was above the quality standard and heavy metal Zn was above the quality standard.